Prevention of Criminal Acts of Corruption in Indonesia - Sonia Vitania Hubah; Bernardus Hanggara Setyananda; M. Hanif Roid Fauzi (Dinasti Research, 2020)
Corruption is one of the biggest problems that is very difficult to eradicate in Indonesia. Indonesia is a country that is rich in natural resources, but Indonesia lacks character than its human resources. Corruption is also one of the obstacles why Indonesia is not currently a developed country. This is because state assets that should be used in the interests of the state, however, by irresponsible people are used for their own interests. Therefore, it is necessary to prevent corruption so that Indonesia can develop into a developed country. The purpose of writing this article is to: (1) know the typology of corruption; (2) knowing the bad effects of corruption in Indonesia; (3) knowing the criminal penalty against the perpetrator of corruption; (4) knowing how to prevent corruption in Indonesia. The writing method used is descriptive qualitative with the data source used by the author, namely library research, which is data obtained from existing literature from books, journals, the internet and other references that are in accordance with the research problem. In preventing corruption itself, of course there needs to be cooperation between the government and the Indonesian people. As the government apparatus who manages the state, it is necessary to manage state assets as well as possible for the interests of the state and society, while the people must believe in and support the work of government. With this cooperation, it is hoped that Indonesia will be free from criminal acts of corruption.